PRODUCTION PERFORMANCE OF INTENSIVE WHITELEG SHRIMP (Penaeus vannamei) FARMING WITH BUSMETIK AND BUTAMIRA METHODS - Diah Ayu Satyari Utami; Adriansyah; I Gede Rezza Mahendra; Wahyu; Meilya Suzan Triyastuti (Universitas Mataram, 2026)
This study evaluated the production performance of intensive whiteleg shrimp (Penaeus vannamei) farming using BUSMETIK (plastic pond, 1600 m²) and BUTAMIRA (household-scale pond, 250 m²) methods at the Marine and Fisheries Polytechnic of Jembrana, Bali. Shrimp were stocked at 370 individuals/m² (BUSMETIK) and 172 individuals/m² (BUTAMIRA) and cultured for 75 days (October–December 2023). Culture management included pond preparation, blind and demand feeding strategies, aeration, water quality control, and probiotic applications. Growth and production performance were assessed through survival rate (SR), average body weight (ABW), average daily growth (ADG), feed conversion ratio (FCR), and water quality parameters. Results showed that both systems supported stable water quality and effective shrimp growth. BUSMETIK ponds demonstrated higher productivity due to greater stocking density, while BUTAMIRA provided efficient production with lower operational inputs, making it suitable for household-scale adoption. Overall, both culture methods proved feasible for small-scale intensive shrimp farming, offering promising strategies to support Indonesia’s shrimp production targets and provide opportunities for smallholder farmers.